Systemic Bevacizumab (Avastin) for Juvenile‐Onset Recurrent Respiratory Papillomatosis: A Systematic Review. (22nd September 2020) - Ryan, Marisa A.; Leu, Grace R.; Upchurch, Patrick A.; Tunkel, David E.; Walsh, Jonathan M.; Boss, Emily F.
Abstract : Objectives: Juvenile onset recurrent respiratory papillomatosis (JORRP) can cause severe or disseminated disease. Surgical treatment may be inadequate. Systemic bevacizumab has shown initial success for severe JORRP. The objective of this systematic review was to assess usage, effectiveness, and safety of this treatment. Methods: We searched PubMed, Embase, and Web of Science for studies of humans with JORRP treated with systemic bevacizumab. Two researchers independently reviewed the studies to determine inclusion and aggregate data on patient characteristics, dosing protocols, treatment response, adverse events, and level of evidence. Results: Of 80 identified articles, 12 studies were included detailing 20 distinct cases. At a mean age of 12.8 years (range = 1–43 years) patients received initial dosing of 5 to 10 mg/kg of bevacizumab followed by ongoing doses at a mean 3‐week intervals (range = 2–5 weeks). All patients had clinically significant disease reduction with reduced need for surgery. Six patients (30%) had complete response in at least one involved anatomic site. Eleven (55%) required no surgery after initiating treatment. There was recurrence in all four patients whose treatment was stopped, but had rapid improvement with treatment resumption. Six (30%) experienced mild or moderate adverse events. Conclusions: Marked improvement in severe JORRP has been reported from systemic bevacizumab. Treatment protocols vary, and treatment discontinuation was not feasible in any reported patient. Based on currently available data, systemic bevacizumab can be considered for severe JORRP as it appears to be well tolerated and effective. A clinical trial could enhance the understanding of its safety and efficacy for this indication. Laryngoscope, 131:1138–1146, 2021